2019
DOI: 10.2166/wst.2019.420
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing anaerobic digestion of dairy and swine wastewater by adding trace elements: evaluation in batch and continuous experiments

Abstract: Trace elements play a critical role for microbial activity in anaerobic digestion (AD) but their effects were probably overestimated in batch tests and should be comparably evaluated in continuous systems. In this study, Fe2+, Co2+, Ni2+, Cu2+ and Zn2+ were added in different concentrations to manure wastewater, and the effects were compared in both batch and continuous systems. The results were used to demonstrate suitable trace element compositions for AD of dairy and swine wastewater, and to compare the out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…During the S3 stage, the soluble iron in R2 increased to 75.8 mg/L, which was higher by 1.4-fold than that of R1 (54.7 mg/L).The raised soluble iron content in R2 may be ascribed to the mitigation of sulfide in the liquid phase, which blocks precipitation of FeS and “releases” free iron, improving the bioavailability of iron for the microorganism. It was reported that addition of a minute amount of Fe 2+ or Fe 3+ has a significantly positive effect on the AD performance of swine and dairy manure. , The raised soluble iron content attained in this study has a positive effect on the methane yield, as shown in Figure .…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…During the S3 stage, the soluble iron in R2 increased to 75.8 mg/L, which was higher by 1.4-fold than that of R1 (54.7 mg/L).The raised soluble iron content in R2 may be ascribed to the mitigation of sulfide in the liquid phase, which blocks precipitation of FeS and “releases” free iron, improving the bioavailability of iron for the microorganism. It was reported that addition of a minute amount of Fe 2+ or Fe 3+ has a significantly positive effect on the AD performance of swine and dairy manure. , The raised soluble iron content attained in this study has a positive effect on the methane yield, as shown in Figure .…”
Section: Resultssupporting
confidence: 58%
“…It was reported that addition of a minute amount of Fe 2+ or Fe 3+ has a significantly positive effect on the AD performance of swine and dairy manure. 37,38 The raised soluble iron content attained in this study has a positive effect on the methane yield, as shown in Figure 5.…”
Section: Resultsmentioning
confidence: 54%
“…The reduction of the area required for the application of nitrogen-rich digestate after the biogas production and the possibility to treat the air stripped digestate in the wastewater plant are other advantages of the combined system AS/AD [41]. The main bacteria in the anaerobic process are hydrogenotrophic Methanocorpusculum, acetoclastic Methanosaeta [88], Methanobacteria, and Methanocorpusculum [89]. Clostridia are generally the most abundant bacteria for hydrolysis and fermentation as they can tolerate high concentrations of volatile fatty acids [89,90], while the Bacilli class easily produces acetate and lactate [88].…”
Section: Air Stripping Applications In Literaturementioning
confidence: 99%
“…The main bacteria in the anaerobic process are hydrogenotrophic Methanocorpusculum, acetoclastic Methanosaeta [88], Methanobacteria, and Methanocorpusculum [89]. Clostridia are generally the most abundant bacteria for hydrolysis and fermentation as they can tolerate high concentrations of volatile fatty acids [89,90], while the Bacilli class easily produces acetate and lactate [88]. Schröder et al [91] used the liquid fraction of the digestate to recover phosphorous and nitrogen by struvite precipitation; then, the effluent was used for the production of ammonium sulphate by air stripping.…”
Section: Air Stripping Applications In Literaturementioning
confidence: 99%
“…Although the most promising technology, especially in the case of GHG emissions from the solid fraction or farmyard manure (mixture of feces, urine and straw), seems to be anaerobic digestion, it is not the most efficient substrate in itself, as its biogas productivity is low [83,84]. Several scientific reports indicate a low efficiency of methane fermentation in relation to manure.…”
Section: Strategy Affecting Thementioning
confidence: 99%